The Characterization of artisanal fisheries of merluccius gayi in the fishing cove of Santa Rosa (Santa Elena province) (Revista Científica Ciencias Naturales y Ambientales, 2017)
During 2011 and 2012, the Instituto Nacional de Pesca (in English, National Fisheries Institute of Ecuador) implemented an Aboard Observer Program with the objective of contributing to both, the fishery and economic knowledge of the Panama hake artisanal fishery, carried out by fishermen from Santa Rosa in the Province of Santa Elena, participating in 1 498 maneuvers, where, through a fishing log, information that allowed to establish that most of their fishing areas are between 02° 15’ to 02° 00’ S and 81° 00’ to 81° 15’ W was obtained and, that their catches fluctuated between 4,695.90 and 20,066.40 kg, from which hake represented 91.9%, while the associated fauna was mainly represented by demersal fish, without observing spatial or temporal variations in its composition. Hake catches would be influenced not only by the availability of the target species, but also by the fishing zone (Los Cachos) and the bait used (squid and pinchagua). Also, the bird capture rate was established, which fluctuated between 0.015 and 0.086 birds/1000 hooks , that is, this fishery would have minimal impact on birds. The monthly profitability was established at $2,061.00; of which $1,030.50 are for the vessel owner and $343.50 for each fisherman. The benefit-cost ratio (BCR) was established at 3.23, which means that it is a profitable activity.
Keywords: bait; fishing zone; abundance; economic profitability